Proceedings of the 6th ACM International Symposium on Pervasive Displays 2017
DOI: 10.1145/3078810.3078831
|View full text |Cite
|
Sign up to set email alerts
|

Investigating how user avatar in touchless interfaces affects perceived cognitive load and two-handed interactions

Abstract: In recent years, touchless-enabling technologies have been more and more adopted for providing public displays with gestural interactivity. This has led to the need for novel visual interfaces aimed at solving issues such as communicating interactivity to users, as well as supporting immediate usability and "natural" interactions. In this paper, we focus our investigation on a visual interface based only on the use of in-air direct manipulations. Our study aims at evaluating whether and how the presence of an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…For instance, Müller et al showed that interactivity can be recognized after less than three seconds using avatars [23]; however, their work considers users of various ages, without an in-depth analysis of children's behaviors. Similar limitations can be found in [8,17,18,33]. In the context of child-computer interaction, other facets of touchless gestural interaction have been investigated, mainly in order to understand the effect of such novel paradigm in learning activities [1,5,26], but also for gaming purposes [4,5,12].…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 93%
See 2 more Smart Citations
“…For instance, Müller et al showed that interactivity can be recognized after less than three seconds using avatars [23]; however, their work considers users of various ages, without an in-depth analysis of children's behaviors. Similar limitations can be found in [8,17,18,33]. In the context of child-computer interaction, other facets of touchless gestural interaction have been investigated, mainly in order to understand the effect of such novel paradigm in learning activities [1,5,26], but also for gaming purposes [4,5,12].…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 93%
“…the inability to understand the interaction modality of the display [8]). Gentile et al showed also that the presence of an avatar makes two-handed interactions more "natural" in the sense that it contributes to a reduction of the cognitive workload while interacting with public displays [17]. However, to the best of our knowledge, prior work has not focused on the use of avatar-based solutions by a specific class of users, such as children.…”
Section: Gestural Interfaces and The Use Of Avatarmentioning
confidence: 99%
See 1 more Smart Citation
“…the inability to understand the interaction modality of the display [13]). Gentile et al showed also that the presence of an avatar makes two-handed interactions more "natural", reducing the cognitive workload while interacting with public displays [21].…”
Section: Interaction With Pervasive Displaysmentioning
confidence: 99%
“…As already mentioned in section 2.1, the use of avatar-based interfaces has many advantages, including the ability of communicating the supported touchless gestural interactivity [33], and the reduction of the perceived cognitive workload, which should contribute to make the interactions more natural [21]. While adding the avatar to a gestural UI is crucial to make it reasonably effective, with touch-based interfaces the affordance of the display and the users' prior experiences can be considered sufficient to overcome these limitations [13].…”
Section: Design Choicesmentioning
confidence: 99%